Modeling of radiative and quantum electrodynamics effects in PIC simulations of ultra-relativistic laser-plasma interaction. (March 2016) - Lobet, M; d'Humières, E; Grech, M; Ruyer, C; Davoine, X; Gremillet, L
Abstract: Next generation of ultra-intense laser facilities will lead to novel physical conditions ruled by collective and quantum electrodynamics effects, such as synchrotron-like emission of high-energy photons and e + e - pair generation. In view of the future experiments performed in this regime, the latter processes have been implemented into the particle-in-cell code CALDER.